The good, the bad, and the ugly: Compliance of e-pharmacies serving India and Kenya with regulatory requirements and best practices. - Gautam Satheesh; Sammy Masibo; Sasi Kumar Tiruttani; Irene Khayoni; Benjamin Palafox; Devaki Nambiar; Jaison Joseph; Emmanuel Kweyu; Abdul Salam; Francis Wafula; Catherine Goodman (PLOS Global Public Health)
As with most technology-driven change, e-pharmacy markets have expanded faster than the pace of regulation, particularly in low- and middle-income countries. We developed and applied a checklist to assess compliance with best practices and regulations by e-pharmacies serving clients in India and Kenya, two countries with contrasting regulatory environments. We defined e-pharmacies as businesses selling prescription-only medicines directly to consumers through websites or apps. We identified the universe of e-pharmacies through online searches, and captured data using a structured questionnaire (Jan-May 2023). We then assessed e-pharmacies against a set of global 'best practice' standards, as well as national regulations (for Kenya) and 'proposed requirements' from local guidelines and draft bills (for India, which had no e-pharmacy-specific regulations). We identified 61 websites and 37 apps serving India, and 26 websites and 3 apps serving Kenya. Regarding best practices, a facility to upload prescriptions was provided by 90% of websites serving India and 58% serving Kenya. Only 16% (India) and 42% (Kenya) provided complete drug information. On average, websites serving Kenya met 8.9 of the 12 (74%) Kenyan regulatory requirements, while those serving India met 7.5 of the 14 (54%) 'proposed requirements'. Only 31% serving Kenya and none serving India displayed required registration numbers. Contrary to regulations/guidelines, many e-pharmacies serving Kenya (62%) and India (34%) listed narcotic/controlled drugs for sale. In both countries, high-traffic websites and e-pharmacies located within the study country had higher mean compliance to regulation and best practices compared to the others. These findings can be leveraged to strengthen enforcement in Kenya and inform the development of a comprehensive regulatory framework in India. We recommend a risk-based regulatory approach, where regulators work with the largely compliant ("good") e-pharmacies, improve enforcement among the partially compliant ("bad"), and eliminate the largely non-compliant ("ugly") from the market.